2018
DOI: 10.1089/humc.2018.133
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-451 Inhibits Glioma Cell Proliferation and Invasion Through the mTOR/HIF-1α/VEGF Signaling Pathway by Targeting CAB39

Abstract: MicroRNAs (miRNAs) are widely expressed and regulate most biological functions. According to several research groups, miR-451 expression is decreased in glioma cells. A previous study also confirmed that miRNA-451 inhibits the PI3K/AKT signaling pathway by directly targeting CAB39, which inhibits glioma cell growth and proliferation and induces apoptosis. However, the specific regulatory mechanism is unclear. Mammalian target of rapamycin (mTOR) is a central regulator of the differentiation, proliferation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 34 publications
1
44
0
Order By: Relevance
“…Interactions between different cell types occurring in-vivo could also explain the differences noted in the expression of the Ang proteins and their receptor Tie2. miR-451 has been shown to inhibit angiogenesis through targeting MIF, calcium-binding protein 39 (CAB39) and IL-6R mediated pathways that influence expression of VEGF-A [16,35,48]. In our study, administration of a miR-451 inhibitor was also associated with increased expression of VEGF-A.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Interactions between different cell types occurring in-vivo could also explain the differences noted in the expression of the Ang proteins and their receptor Tie2. miR-451 has been shown to inhibit angiogenesis through targeting MIF, calcium-binding protein 39 (CAB39) and IL-6R mediated pathways that influence expression of VEGF-A [16,35,48]. In our study, administration of a miR-451 inhibitor was also associated with increased expression of VEGF-A.…”
Section: Discussionmentioning
confidence: 52%
“…Normal alveolar development has been shown to be dependent on angiogenesis [4,32,33] and dysregulated vascular growth is a well-established feature of the BPD phenotype [1,4]. miR-451 is a miRNA that has been shown to inhibit the expression of pro-angiogenic and antiapoptotic mediators such as MIF, IL-6R and YWHAZ in a variety of different malignant cell types and tumors [14,16,18,34,35]. In tumors, reduced expression of miR-451 and increased expression of MIF is associated with increased likelihood of progression [15,36]; however, in preterm infants, increased expression of MIF is linked to a reduced risk for BPD [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Among which, miR-451 is a frequently investigated miRNA in glioma. According to several research groups, miR-451 expression is repressed in glioma tissues and cells [18,19]. Besides, miR-451 acted as a tentative switch in mediating glioma cells growth and migration [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…30 MiR-451 suppressed glioma cell proliferation and invasion by blocking the mTOR/HIF-1α/VEGF pathway through regulating CAB39 expression. 31 Propofol has also been found to exert anti-tumor functions via regulating miRNAs in many types of tumors. For instance, Yu et al found propofol promoted cell apoptosis in breast cancer via downregulating miR-24.…”
Section: Discussionmentioning
confidence: 99%